2019
DOI: 10.1111/padm.12612
|View full text |Cite
|
Sign up to set email alerts
|

Does transformational leadership stimulate user orientation? Evidence from a field experiment

Abstract: While doing good for specific citizens and users is often considered a powerful motivator among public service employees, little research has rigorously evaluated how public managers can promote individualized prosocial motivation. We follow recent studies on the behavioural implications of ‘user orientation’ to explore how public managers can use a specific leadership strategy—transformational leadership—to reinforce employees' individualized prosocial motivation. Combining a field experiment with 80 childcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
(83 reference statements)
0
8
0
1
Order By: Relevance
“…This study investigates longer‐term leadership training effects on leadership behavior (3 months after end of training) and objective school performance (1 year after end of training). Effects of training creates value through perceived leadership behavior (An et al, 2020), motivation (Bro & Jensen, 2020), and value congruence (Jensen, 2018), but the value of leadership training should ultimately be assessed by performance effects. These are, nonetheless, complex and multidimensional (Andersen, Heinesen, & Pedersen, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigates longer‐term leadership training effects on leadership behavior (3 months after end of training) and objective school performance (1 year after end of training). Effects of training creates value through perceived leadership behavior (An et al, 2020), motivation (Bro & Jensen, 2020), and value congruence (Jensen, 2018), but the value of leadership training should ultimately be assessed by performance effects. These are, nonetheless, complex and multidimensional (Andersen, Heinesen, & Pedersen, 2016).…”
mentioning
confidence: 99%
“… The leadership experiment has been investigated in six published studies: An et al, 2019, 2020; Jensen, 2018; Jensen, Andersen, and Jacobsen, 2019a; Jacobsen & Andersen, 2019; Bro & Jensen, 2020. …”
mentioning
confidence: 99%
“…Transformationsledelse begrunder en bestemt handling ved at knytte opnåelsen af et højere formål til handlingen . Det kan vaere at gøre en positiv forskel for den enkelte borger (Bro og Jensen, 2020) eller samfundet som helhed (Wright, Moynihan og Pandey, 2012). Med andre ord fremlaegger lederen en intention over for følgerne og gør det klart, hvad formålet med en given handling er (Andersen og Jakobsen, 2019: 291-293).…”
Section: Hvad Er Personlig Ledertrovaerdighed?unclassified
“…Accumulating evidence suggests that TFL is particularly effective in the various national police organizations where it has been studied (see Haberfeld 2006). TFL seems appropriate for developing long-term service-and citizen-oriented relationships (Liao and Chuang 2007;Liaw, Chi, and Chuang 2010;Bro and Jensen 2020). Furthermore, prior research has shown that TFL, with its emphasis on a shift 'from personal goals to collective goals, from personal identity to collective identity, from self-interest to collective interest' (Jiao, Richards, and Zhang 2011, 14), is relevant and prevalent in public organizations, such as in police organizations, where there are strong expectations of group loyalty and commitment to collective citizenship (Campbell, Lee, and Im 2016;Sun and Wang 2017).…”
Section: Introductionmentioning
confidence: 99%